New data processing strategy for intelligent CNC machine tool controller using function block technology - Othman, Muhammad Azri (2022)
Enhancement in product data interoperability and flexibility of Computer Numerical Control (CNC) architecture to accommodate the trend toward digitalise industrial manufacturing in the era of Industry 4.0 are very much desired as key driven technologies for the development of new generation CNC systems. Large body of works to improve or even replace the existing CNC data model, that is, G-codes, have been reported by many researchers. It is well-known that this low-level coded data model technology has many limitations to achieving new CNC system especially where open, agile, distributed, interoperable and intelligent are required. The emerging standards like ISO 14649 and ISO 10303 (AP238), also known as STEP-NC, present an opportunity to revolutionize the way CNC machines are traditionally programmed and give promising alternatives to G-codes. Thus, this research proposed a direct integration of decision-making and control abilities of the CNC controller architecture. Therefore, a new data processing unit (DPU) architecture was developed using IEC 61499 function block technology. The role of the proposed DPU evolves from purely functional to decoded part program into flexible or even automatically reconfiguring its execution structures and provides intelligent functions in the case of occurrences of external user demands and/or internal faults. It works with STEP-NC data model and can automatically generate a set of required machining data to be executed on a machine tool. Three simple feature geometries consisting of planar face, closed pocket and round hole, with different machining strategies such as bidirectional, contour-bidirectional and contour milling that constitute a set of machining data were generated by the prototype systems. All sets of data were simulated using MATLAB developed interfaces and later validated on actual machining process using aluminium A6041 workpiece. Based on the machining product, all the desired features with their predetermined machining strategies were successfully machined and resulted in RMSE values of 0.0032mm and 0.0047mm, 0.0164mm and 0.0147mm, and 0.0020mm and 0.0037mm for x and y axes respectively. As conclusion, the system has a layered structure, making it easy to manage and extend. It has been proven that function block technology can provide enough intelligent functions to support the creation of next-generation CNC that is more open, adaptable, flexible, and interoperable.